Modular two-look blouse design using Jumputan and Indigo–Tingi Dyeing for sustainable fashion - Amelia Estriana Ramadhani; Sugiyem Sugiyem (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
The fashion industry increasingly demands sustainable alternatives that preserve cultural heritage. This study addresses the gap sustainably by integrating traditional Indonesian batik with contemporary modular design. Using a 4D R&D approach, a 2-look modular blouse was developed with jumputan cross-tie batik and natural indigo-tingi dyeing on organic cotton. Consumer preference testing with 60 respondents (the majority, 58.3%, aged 21-24 years) across Indonesia showed a strong preference for casual design (72 favorable ratings) over semi-formal (42 ratings). The sustainability concept received 75% perfect-fit ratings, with 92% approving the organic cotton material for its comfort, breathability, and suitability for tropical climates. However, the IDR 320,000 price point showed mixed acceptance: 58% found it acceptable, while 43% expressed affordability concerns, particularly among students. Results confirm market viability for sustainable modular fashion that integrates traditional techniques, though the pricing strategy requires refinement to reach student segments. Limitations include geographic concentration and age demographic skew. This research demonstrates the market viability of conventional textile techniques in contemporary sustainable fashion.